Reduction of miR‐212 contributes to pituitary adenoma cell invasion via targeting c‐Met - Hong‐Yan Wang; Huai‐Qing Gao (Kaohsiung Journal of Medical Sciences)
Abstract The current study aimed to evaluate the expression and role of miR‐212 in the progression of pituitary adenoma (PA), thereby providing a theoretical basis and potential therapy methods for PA patients. Our data showed that miR‐212 levels were significantly reduced in PA tissues than normal pituitary tissues. However, no significant difference was identified in the serum of PA patients and healthy control. In addition, the expression of miR‐212 in invasive PA was significantly lower than that in noninvasive and normal pituitary tissues. Moreover, the level of miR‐212 was decreased with the increase of tumor invasion. Meanwhile, the expression of miR‐212 in giant adenomas was significantly lower than that in macroadenomas and microadenomas. Furthermore, inhibition of miR‐212 significantly enhanced the proliferation and invasive capacity of GH3 cells. Dual luciferase reporter assay and western blot analysis confirmed that c‐Met was a target gene of miR‐212. More importantly, upregulation of c‐Met significantly prompted PA cell proliferation mainly as a result of the enhanced level of phosphorylation of AKT. This effect could be abolished when c‐Met was silenced in GH3 cells. In summary, reduced miR‐212 expression in PA contributed to abnormal cancer cell proliferation and invasion mainly by targeting c‐Met.